In vitro metabolism, reaction phenotyping, enzyme kinetics, CYP inhibition and induction potential of ataluren. Issue 2 (20th March 2020) - Kong, Ronald; Ma, Jiyuan; Hwang, Seongwoo; Moon, Young‐Choon; Welch, Ellen M.; Weetall, Marla; Colacino, Joseph M.; Almstead, Neil; Babiak, John; Goodwin, Elizabeth
Abstract: Ataluren promotes ribosomal readthrough of premature termination codons in mRNA which result from nonsense mutations. In vitro studies were performed to characterize the metabolism and enzyme kinetics of ataluren and its interaction potential with CYP enzymes. Incubation of [ 14 C]‐ataluren with human liver microsomes indicated that the major metabolic pathway for ataluren is via direct glucuronidation and that the drug is not metabolized via cytochrome P450 (CYP). Glucuronidation was also observed in the incubation in human intestinal and kidney microsomes, but not in human pulmonary microsomes. UGT1A9 was found to be the major uridine diphosphate glucuronosyltransferase (UGT) responsible for ataluren glucuronidation in the liver and kidney microsomes. Enzyme kinetic analysis of the formation of ataluren acyl glucuronide, performed in human liver, kidney, and intestinal microsomes and recombinant human UGT1A9, found that increasing bovine serum albumin (BSA) levels enhanced the glucuronidation Michaelis‐Menten constant (Km ) and ataluren protein binding but had a minimal effect on maximum velocity (Vmax ) of glucuronidation. Due to the decreased unbound Michaelis‐Menten constant (Km, u ), the ataluren unbound intrinsic clearance (CLint, u ) increased for all experimental systems and BSA concentrations. Human kidney microsomes were about 3.7‐fold more active than human liver microsomes, in terms of CLint, u /mg protein, indicating that the kidney is also a key organ for the metabolism and disposition of ataluren in humans. Ataluren showed no or little potential to inhibit or induce most of the CYP enzymes.